Akuntabilitas dan kinerja instansi pemerintah: semu atau nyata? - Muhammad Ahyaruddin; Rusdi Akbar (Jurnal Akuntansi dan Auditing Indonesia, 2017)
This research aims to analyze factors driving the accountability and performance of government as well as exploring qualitatively about accountability and performance of government agencies. In particular, this study examines the effect of incentives, regulations, and management commitment on government accountability and performance. Mixed method approach was used to answer research questions. Hypotheses were tested using SEM-PLS. Data analysis of the study involved 137 SKPD officers in districts/cities in Yogyakarta Special Region (DIY) and five respondents as key informants. The results of the study found that management commitment has significant effect on accountability and government performance. In addition, regulatory also have significant effect on accountability. The findings also reveal the coercive pressure that exists in implementing accountability and government performance. This concludes that reporting of accountability and government performance in DIY was only limited to the formalities to meet regulatory obligations, so that this indicates a pseudo-performance. In the context of institutional theory, this study demonstrates significant contribution to the development of institutional isomorphism in public sector organizations, particularly local governments.